Adolescent Suicide Ideation, Depression and Self-Esteem: Relationships to a New Measure of Gender Role Conflict - O’Beaglaoich, Cormac; McCutcheon, Jessica; Conway, Paul F.; Hanafin, Joan; Morrison, Todd G. (Frontiers in Psychology, 2020)
Among 15-24 year olds in Ireland, completed suicide was responsible for 4.1 times more male deaths than female deaths in 2014 (WHO, 2017). Few international research studies have investigated the relationship between masculinity (as assessed by a measure of gender role conflict [GRC]) and suicide ideation, and none have done so with Irish adolescents. Therefore, the purpose of the current study was to investigate the relationships between a new measure of GRC developed specifically for use with Irish adolescents (I-GRCS-A; O’Beaglaoich, Kiss, Ní Bheaglaoich & Morrison, 2016), and depression, self-esteem, and negative/protective suicide ideation. A sample of 176 adolescent boys (M = 16.9, SD = 0.94) from a non-clinical population participated in the study. Regression analyses and tests of mediation revealed that depression significantly mediated the relationship between GRC and negative suicide ideation, whilst self-esteem and depression significantly mediated the relationship between GRC and positive suicide ideation. Implications and limitations of the current study are outlined and directions for future research are discussed.